2020
DOI: 10.1177/1120672120957590
|View full text |Cite
|
Sign up to set email alerts
|

Clear subretinal fluid in a case of non-neovascular early-onset drusen: Swept-source imaging evaluation

Abstract: A 50-year-old male presented with recent metamorphopsia in the right eye. Fundus examination revealed bilateral multiple cuticular drusen along with few large colloid drusen (phenotype 3 cuticular drusen). No vitelliform material was evident in the macula in either eye. Fluorescein angiography (FA), indocyanine green angiography (ICGA) did not demonstrate a macular neovascularization (MNV) in either eye. Swept-source optical coherence tomography (SS-OCT) revealed sub-retinal pigment epithelial (RPE) drusen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…For instance, by applying this ultrawide field technique, we recently reported a peculiar pattern of vitritis along the vitreous fibrils in cases of vitreoretinal lymphoma (Figure 5). 52 In another paper, the assessment of vitritis with this technique was found to well correlate with the grade of vitritis observed clinically. 53 This application may provide an additional tool for monitoring the grade of vitreous haze, which is one of the main end-points in clinical trials for uveitis.…”
Section: Ultrawide Field Imagingmentioning
confidence: 90%
See 4 more Smart Citations
“…For instance, by applying this ultrawide field technique, we recently reported a peculiar pattern of vitritis along the vitreous fibrils in cases of vitreoretinal lymphoma (Figure 5). 52 In another paper, the assessment of vitritis with this technique was found to well correlate with the grade of vitritis observed clinically. 53 This application may provide an additional tool for monitoring the grade of vitreous haze, which is one of the main end-points in clinical trials for uveitis.…”
Section: Ultrawide Field Imagingmentioning
confidence: 90%
“…Thus, OCTA can be serially used in assessing the treatment response in eyes with VKH, adding significant value alongside OCT and other tests. 38,52 In eyes with acute CSC, the authors observed no choriocapillaris flow deficit on OCTA or ICGA. In certain eyes, areas of PED appeared as a "flow deficit" area on OCTA, but this hypo-reflectivity on OCTA was due to inaccurate segmentation in areas of PED (not due to true ischemia).…”
Section: Differentiating Vogt-koyanagi-harada's Disease and Central S...mentioning
confidence: 96%
See 3 more Smart Citations